The Effect of Organizational Justice Perception on Polices’ Performance - Jankingthong, Korkaew (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
Within a work environment, employees typically expect to see the outcomes of their contributions. If they perceived an inequitable return for their contributions, people might feel like they have been treated unfairly. This situation consequently causes a negative influence on individuals’ behavior in a manner that would affect their work performance, thus lead to a negative effect on the organization at the end. The purposes of this research were 1) to study the perception of organizational justice of policemen in Thailand and 2) to construct the predictive equations of the effect of organizational justice on polices’ performance. Samples were 396 policemen working in Southern Thailand. Data were collected using a questionnaire. The reliability of the instruments ranked from 0.72 to 0.95. The study employed the stepwise multiple regression analysis technique. Results revealed that policemen’s overall perception of organizational justice and their perception of each of the three dimensions (distributive, procedural justice, and interactional justice) were at a high level. In constructing a predictive equation, it was found that the best predictive variables included: procedural justice (X2) and interactional justice (X3), with a multiple coefficient (R) at 48 and the predicting power was 22.9 percent. Only two variables significantly predicted polices’ performance at the .001 and .05 level, respectively. Then, the predictive equation was constructed in a row-score form as below: Y = 2.670 + .236 X2 + .093 X3